Experimental study of characteristics of bimetallic Pt–Fe nano-particle fuel cell electrocatalyst. (September 2015) - Yao, Jun; Yao, Yufeng
Abstract: The characteristics of 1.5 wt% Platinum (Pt) loading on Fe incorporated Y zeolite (Pt–Fe/Y zeolite) nano-electrocatalysts have been experimentally studied by the extended X-ray adsorption fine structure (EXAFS) and cyclic voltammetry (CV) techniques using Nafion @ bound electrode to determine Pt electrocatalytic performance in direct methanol fuel cell. The Pt particle size was found to be small in electrochemical environment (0.7 nm with 55 atoms). Study implies that the Pt electrocatalytic performance can be affected by the Pt cluster electron deficiency, due to the change of Pt particle size associated with the lattice strain energy. The CV measurement in the hydride region indicated higher Pt dispersion for Pt–Fe/Y zeolite electrocatalyst chemically reduced in H2 at 400 °C (15PtFeancr4), compared to that of Pt/Y zeolite reduced at 400 °C (15Ptancr4) and Pt–Fe/Y zeolite electrocatalysts reduced at 300 °C (15PtFeancr3), respectively. This provided further implication that the chemical reduction temperature would be important for achieving a higher Pt dispersion. The present study has revealed two possible electron transfer pathways that might contribute to the Pt electronic conduction: (1) the surface mobility of adsorbed species; (2) the hydrogen atoms/H + ion spillover through the zeolite framework and on the electrode surface, despite the DC insulator nature of zeolite. Highlights: Determine Pt electrocatalytic performance in fuel cell. Experimentally study of Fe incorporated Pt nano-particle structure on zeolite. Pt local atomic structure investigated by EXAFS and cyclic voltammetry. Effect of auxiliary metal function of Fe H.